Perforated Carcinoma in the Gastric Remnant: A Case of Conservative Treatment Prior to Successful Curative R0 Resection. (29th August 2016) - Yuu, Ken; Kawashima, Hiroshi; Toyoda, Sho; Okumura, Satoshi; Yamamoto, Kansuke; Mizumura, Naoto; Ito, Aya; Maehira, Hiromitsu; Imagawa, Atsuo; Ogawa, Masao; Kawasaki, Masayasu; Kameyama, Masao
Abstract : An 80-year-old man who had undergone distal gastrectomy and Billroth-II gastrojejunostomy 38 years previously, for a benign gastric ulcer, was diagnosed with remnant gastric cancer based on upper gastrointestinal endoscopy findings. He presented at our emergency department with acute-onset epigastric pain due to perforated remnant gastric cancer. Conservative medical management was selected, including nasogastric tube insertion, antibiotics, and proton pump inhibitors, because his peritonitis was limited to his epigastrium and his general condition was stable. Twenty-one days after the perforation occurred, curative total remnant gastrectomy and D2 lymphadenectomy were performed. Adhesion between the lateral segment of the liver and the dissected lesser curvature of the gastric remnant may have contributed to the peritonitis in this case, which was limited to the epigastrium. This is the first report of perforated remnant gastric cancer in which conservative treatment was effective prior to curative resection. The protocol reported here may be of use to other clinicians who may encounter this clinical entity in their practices.